The effectiveness of a proposed strategy according to the Fraunhofer model of knowledge management in the achievement of second intermediate female students in mathematics - Ahmed Abdullah Misharar, Azraa; Fouad Jawad Al-Ameer, Lina (Edelweiss Applied Science and Technology, 2024)
The goal of the research is to identify the effectiveness of using a proposed strategy according to the Fraunhofer model of knowledge management in mathematics achievement for second-grade female students in middle and high schools affiliated with the General Directorate of Education in Baghdad / Al-Karkh II. The objective was to prove the following null hypothesis: "The average scores of the experimental group who will study with the proposed strategy according to the Fraunhofer model and the scores of the control group students who will study in the usual way in the mathematics achievement test are not statistically significant different at the significance level (0.05)." The General Directorate of Education of Baghdad / Al-Karkh II identified the research population, which represents middle and secondary schools for girls. Sayyida Zainab (peace be upon her) middle school was specifically selected as the research sample, which was divided into two groups and included sixty-one female students in the second middle grade. For the experimental group, represented by Section (A), there were thirty-three female students; for the control group, represented by Section (C), there were twenty-eight female students. Achievement test was developed to gather data for the study. Its final form included 36 objective items of the multiple choice type with four alternatives. Parity was carried out statistically between the female students of the experimental and control groups in the variables (previous achievement in mathematics, previous mathematical knowledge, intelligence). Appropriate statistical techniques were applied when administering the test to the female students in the experimental and control groups (difficulty and ease coefficient, discrimination coefficient, efficacy of alternatives). After the two researchers applied suitable statistical techniques to analyze the data and administer a test like the Leaven’s test, the results showed that teaching with the suggested strategy according to the Fraunhofer model of knowledge management has a significant impact in improving the achievement of the female students of the experimental group compared to the control group. Its psychometric properties were acknowledged.